Proteobacteria, Acidobacteria, and Chloroflexi bacteria from Antarctic soils survive under simulated tropical conditions - Chua, Chuen Yang; Wong, Clemente Michael Vui Ling; González-Aravena, Marcelo; Lavin, Paris; Cheah, Yoke Kqueen (Polish Academy of Sciences Chancellery, 2022)
The human movement to and from Antarctica has increased significantly in recent decades, particularly to the South Shetland Islands, King George Island (KGI), and Deception Island (DCI). Such movements may result in unintentional soil transfer to other warmer regions, such as tropical countries. However, the ability of Antarctic bacteria to survive in tropical climates remained unknown. Hence, the objectives of this work were (i) to determine the bacterial diversity of the soils at the study sites on the two islands, and (ii) to determine if simulated tropical-like growth climate conditions would impact overall diversity and increase the abundance of potentially harmful bacteria in the Antarctic soils. KGI and DCI soils were incubated for 12 months under simulated tropical conditions. After 6 and 12-months, samples were collected and subjected to metagenomic DNA extraction, 16S rDNA amplification, sequencing, and alignment analysis. The 12-month denaturing gradient gel electrophoresis (DGGE) analysis revealed changes in fingerprinting patterns and bacterial diversity indices. Following that, bacterial diversity analyses for KGI and DCI soils were undertaken using V3-V4 16S rDNA amplicon sequencing. Major bacterial phyla in KGI and DCI soils comprised Actinobacteria, Proteobacteria, and Verrucomicrobia. Except for Proteobacteria in KGI soils and Acidobacteria and Chloroflexi in DCI soils, most phyla in both soils did not acclimate to simulated tropical conditions. Changes in diversity were also observed at the genus level, with Methylobacterium spp. predominating in both soils after incubation. After the 12-month incubation, the abundance of potentially pathogenic bacteria such as Mycobacterium, Massilia, and Williamsia spp. increased. Overall, there was a loss of bacterial diversity in both Antarctic soils after 12 months, indicating that most bacteria from both islands sampling sites cannot survive well if the soils were accidentally transported into warmer climates.